Distribution and Activation of cAMP- and cGMP-Dependent Protein Kinases in Highly Purified Human Platelet Plasma and Intracellular Membranes - El-Daher, Samer S; Eigenthaler, Martin; Walter, Ulrich; Furuichi, Teiichi; Miyawaki, Atsushi; Mikoshiba, Mikoshiba; Kakkar, Vijay V; Authi, Kalwant S (Thrombosis and Haemostasis, 1996)
Previously cAMP- and cGMP-dependent protein kinases (cAMP-PK, cGMP-PK) have been found predominantly associated with the particulate fraction in human platelets. We now report the distribution and activation of cAMP-PK and cGMP-PK in highly purified fractions of human platelet plasma (PM) and intracellular membranes (IM) prepared using high voltage free flow electrophoresis. Two non-hydrolys-able analogues of cAMP and cGMP namely Sp-5,6-DCl-cBiMPS and 8-p-CPT-cGMP have been used to activate cAMP-PK and cGMP-PK respectively. Addition of either agonist with [γ32P]ATP stimulated the endogenous activity of cAMP-PK or cGMP-PK in PM but not in IM. With PM Sp-5,6-DCl-cBiMPS stimulated the phosphorylation of protein substrates of Mr 16,22,24,46-50,66,90,160 and 250 kDa. A specific peptide inhibitor of cAMP-PK inhibited the phosphorylation of all of the substrates by Sp-5,6-DCl-cBiMPS. 8-pCPT-cGMP also induced the phosphorylation of a number of substrates particularly 16,22, 46-50, 90 and 250 kDa proteins. Inclusion of the cAMP-PK inhibitor peptide totally blocked the phosphorylation of the 16 and 22 kDa proteins, partially inhibited phosphorylation of 46-50 and 90 kDa proteins and had no effect on the 250 kDa protein indicating the 46-50, 90 and 250 kDa proteins were also cGMP-PK substrates. Western blotting with antibodies to cGMP-PK and the catalytic subunit of cAMP-PK revealed the presence of the kinases to be exclusively associated with PM with no detection in IM.The presence of cAMP-PK substrates in IM was investigated by exogenous addition of catalytic subunit of cAMP-PK. Phosphoproteins of Mr 16, 22, 27, 30,45, 75,116 and 250 kDa were detected. A range of antibodies to cAMP-PK substrates were used to identify and localise the substrates. These antibodies revealed GPIb and VASP to be exclusively associated with PM fractions. Rap IB was also predominantly associated with PM with a small level detected in IM. Antibodies to the IP3 receptor (18A10 and 4C11) revealed the protein to be predominantly associated with IM. Additionally the antibody 4C11 recognised a 230 kDa protein band in PM that was not seen in IM. From the known specificity of these antibodies the results confirm the presence of a type IIP3 receptor in IM and a distinct (possible type III) IP3 receptor with the PM. the 16, 22, 27, 30, 75 and 116 kDa proteins in IM represent nwly detected substartes for camp-pk of presently unknown identity.